Equianalgesic Oxycodone, Continuous Intravenous Morphine in Post- Long Bone Surgery - Franz Josef Tarigan; Hanafie, Achsanuddin; Arifin, Hasanul; Wijaya, Dadik Wahyu (Talenta Publisher, 2019)
Oxycodone and morphine are powerful analgesic drugs used for post-operative pain management. There is no studies have been conducted to assess the dose equivalency between the two drugs. To get an equianalgesic dose of Oxycodone and Morphine. This study was using a double-blind randomized clinical trials, 48 samples, ages 21-60 years, PS ASA I-II, which will get an elective orthopedic surgery using general anesthesia tech-niques. Oxycodone (group A) : Morphine (group B) (Initial 5mg than continuous 1 mg/hour : initial dose 4mg than continuous 0,5 mg/hour). Average drug dose for group that takes morphine and oxycodone (3.90 ± 0.46 mg : 1.46 ± 0.51 mg). No significant difference between the average dose (p <0.05). Equianalgesic dosein group Oxycodone and Morphine is 1.4 mg: 3.9mg.